FREEDOM AND RESPONSIBILITY OF PRESS EXPRESSION IN HISTORICAL REVIEW - Putri Indah Lestari; M. Rafli Zulfikar; Naia Zattira Ba'ayesh; Syahla Hidayah; Erwan Efendi (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
During the New Request period, the press was controlled by Regulation No. 11 of 1966, Regulation No. 4 The year 1967 and Regulation No. 21 of 1982 which was a result of the Suharto system that severe, while in the Renewal time after the defeat of Suharto press life was forced Regulation No. 40 of 1999 concerning the Press is brimming with happiness. During the New Request period produce a dictator press framework all the while assuming a pretense of the Pancasila press framework, to be specific a free press what's more, capable, so thus press opportunity is seriously abridged through Breidel and placed him in an enemy of government jail. In the Reconstruction period the press framework went to The liberal press framework is with the rapture of opportunity that is an excessive amount of in light of the fact that it does not exist anymore harsh administrative arrangements. During the New Request period (1966–1998), the public authority zeroed in on parts of security. governmental issues to help improve public. Guidelines in regards to the press are controlled by Regulation No. 11 of 1966 concerning Fundamental Arrangements for the Press related to Regulation No. 4 of 1967 related to Regulation No.21 of 1982, and furthermore, Pastor of Data Guideline No. 1 of 1984 concerning Grants Press Distributing Business (SIUPP), which delivers a dictatorial press all the while assuming a pretense of the Pancasila press framework, specifically a press framework thattyrant, then the press opportunity is seriously confined. specifically through breidel (scratch-off of SIUPP). Furthermore, they tossed the individuals who were behind bars. thought about the enemy of government. In the mean time in the period Change (1998-present), requests for change The fact that blows makes the law one has been areas of strength since May 1998. In like manner in the field of political regulation, including press opportunity. In this state, it was conceived. Regulation No. 40 of 1999 concerning the Press made by the lawmaking body because of the political race considered exceptionally fair. In view of Regulation No. 40 of 1999 concerning the Press, a liberal press framework, to be specific, with the elation of opportunity that goes excessively far in light of the fact that There are not any more harsh administrative arrangements.